URGENSI PENDIDIKAN KARAKTER DI LEMBAGA PENDIDIKAN - Maulana, Didik (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2015)
Crisis in Indonesia is getting messy is believed to be due to a lack of character. Indeed, many feel that this national has lost its character. But when asked what the character was, we sputtered. Character, something that should be know, but most do not want to know. Something ver important, but most of us underestimate, something that is very necessary, but in the fact most of us even laughing. Awareness of various circles, especially educators are expected to instill character in every educational institution, given the character of the nation that has decreased or away from the values of kindness.